The God that failed : six famous men tell how they changed their minds about communism - Koestler, Arthur; Wright, Richard; Fischer, Louis; Silone, Ignazio; Gide, AndrÃ©; Spender, Stephen; Crossman, Richard (New York : Bantam Books, 1952)
Bibliotheek Camille Huysmans
Engels
Monografie